Developing front office service as benchmarking at Discovery Kartika Plaza Hotel - Luh Putu Ayunita Kartini; Ni Nyoman Triyuni; Nyoman Mastiani Nadra (Journal of Applied Sciences in Travel and Hospitality, 2021)
The purpose of this research is to know the implementation of service attributes and the benchmark of Front Office Department at Discovery Kartika Plaza Hotel to develop the services quality in front office department. The method of the data collection applied for this research are participant observation, interview, questionnaire, guests comment and documentation. This research used 30 respondents of front office staffs and the data was analyzed qualitative descriptively. The result of the study identified that, the implementation of service attributes in all sections in front office department is very good and all sections have score more than 4,0. The benchmark is Guest Service Agent with average score 4.95 or 20.89%. The lowest section is Telephone Operator with average score 4.43 or 18.69% because during working not care with SOP, not implement the service attribute so well, and the staffs have less knowledge on IT. The front office department should do the improvement and development on the service quality and the attitude of the staff. As the benchmark, the Gust Service Agent has done many ways to improve the service quality. The best way to improve the service quality, the hotel can use the benchmark as the standard to find the best strategy and technic how to improve and develop the service quality of the front office department at Discovery Kartika Plaza Hotel. The Guest Service Agent as the benchmark in front office department should be maintain their service as standard of the other sections to develop the service quality in the front office department at Discovery Kartika Plaza Hotel.